Implementation of International Standards in Russia's Foreign Trade Statistics - N. E. Grigoruk (MGIMO University Press, 2015)
The article analyzes the basic documents of international organizations in recent years, which have become the global standard for the development and improvement of statistics of foreign economic relations of most countries, including the Russian Federation. The article describes the key features of the theory and practice of modern foreign trade statistics in Russia and abroad, with an emphasis on the methodological problems of its main parts - the external trade statistics. It shows their interpretation in the most recent recommendations by UN statistical apparatus and other international organizations; considers a range of problems associated with the implementation of the national statistical practices of countries, including Russia and the countries of the Customs Union, the main international standard of foreign trade statistics - UN document "International Merchandise Trade Statistics". The main attention is paid to methodological issues such as: the criteria for selecting the objects of statistical accounting in accordance with international standards, quantitative and cost parameters of foreign trade statistics, statistical methods and estimates of commodity exports and imports, the problems of comparability of data; to a comparison of international standards in 2010 with documents on key precursor methodology of foreign trade statistics, characterized by the practice of introducing these standards in the foreign trade statistics of Russia and the countries of the Customs Union. The article analyzes the content given in the official statistical manuals of Russia foreign trade and foreign countries, covers the main methodological problems of World Trade in conjunction with the major current international statistical standards - System of National Accounts, Manual on Statistics of International Trade in Services and other documents; provides specific data describing the current structure of Russian foreign trade and especially its position in international trade in goods and services.